DLK1, delta-like 1 homolog (Drosophila), regulates tumor cell differentiation in vivo - Begum, Asma (2011)
The stem cell-like characteristics of tumor cells are not only essential for tumor development and malignant progression, but also significantly contribute to therapy resistance. However, it remains poorly understood how cancer cell differentiation or stemness is regulated in vivo. We investigated the role of the stem cell gene DLK1, or delta-like 1 homolog (Drosophila), in the regulation of cancer cell differentiation in vivo using neuroblastoma (NB) xenografts as a model. We found that loss-of-function mutants of DLK1 significantly enhanced NB cell differentiation in vivo likely by increasing the basal phosphorylation of MEK and ERK kinases, a mechanism that has been shown to facilitate neuronal differentiation. We also found that DLK1(+) cells are preferentially located in hypoxic regions. These results clearly demonstrate that DLK1 plays an important role in the maintenance of undifferentiated, stem cell-like phenotypes of NB cells in vivo.